La carga de la prueba en el despido intempestivo, es constitucional y legal que la presente y justifique el trabajador - Robalino Paucar, Adrián Bladimir (2017)
The present research aims to address a social problem that is dealt with by labor laws, which is "The burden of proof in untimely dismissal." Because there is no specific rule regulating the burden of proof on untimely dismissal, various and contradictory pronouncements have been given and continued on this procedural right; Those who opt for the application of the rules of evidence of the Code of Civil Procedure and now the General Organic Code of Processes argue that the fact of untimely dismissal must be proven by whoever claims it; While those who opt for the doctrine and defend the essence of work as a constitutional right of economic and social type, argue that the positive fact of untimely dismissal, being the domain of the employer, who is the one who can plan and execute it in The conditions and moment that he creates, it is his obligation to prove his denial or falsity of the fact. We approach the Constitution, as the Supreme Norma, from which we extract the recognition and special protection of work activity, which, even, is given the rank of a human right; With this we descend, in relation to the hierarchy of laws, to make a theoretical, critical and normative study on the procedural principle of the burden of proof, applied in labor matters, from the experience of our country and comparative law, To amend the Labor Code through the implementation of a specific rule that expressly determines the cases in which the procedural principle of reversal of the burden of proof must be applied.